ANALYSIS BREAK-EVEN POINT OF TOFU AGROINDUSTRY - Putra, Ade Fikri Maulana; Noor, Trisna Insan; Isyanto, Agus Yuniawan (Universitas Galuh, 2023)
The tofu agroindustry Sumber Rezeki is one of the tofu industries that is still active in Balokang Village, Banjar District, Banjar City which has been established since 1999 until now, but until now the craftsmen do not know clearly about financial management, profits and business success. Research purposes is to find out: (1) the cost and income of tofu agroindustry; (2) the amount of R/C; and (3) the amount of the break-even point of revenue, the break-even point of production volumes and the break-even point of prices in one production process. The type of research used is a qualitative method. The results showed: (1) The production cost of the tofu agroindustry